If AB = BA and p is a nonnegative integer, prove that (AB)^ p = A^p B^p. I've been sitting on this one for an hour and I'm just ridiculously confused!
Follow Math Help Forum on Facebook and Google+
Originally Posted by Brokescholar If AB = BA and p is a nonnegative integer, prove that (AB)^ p = A^p B^p. I've been sitting on this one for an hour and I'm just ridiculously confused! by induction over p. if p = 1 it's clear. assuming it's true for p, then:
Awesome! You're a genius thanks for the help!
View Tag Cloud